Tinjauan Teologis Mengenai Makna Kata “Immanuel” Menurut Kirill dari Aleksandria [Theological Review on the Meaning of the Word "Immanuel" According to Cyril of Alexandria] - Sarah Apriliana; Hendi Hendi (Diligentia: Journal of Theology and Christian Education, 2022)
In the Old Testament, there is a prophecy about God that gave a sign that a virgin would conceive and give birth to a son, and she would name him Immanuel. Although the term sounds familiar, the word Immanuel is only mentioned 3 times in the Bible, namely in Isaiah 7:14, Isaiah 8:8 and Matthew 1:23. The word "Immanuel" itself literally means "God with us." This word is a designation that refers to the presence of God in accompanying His people. This article will discuss further the meaning of the word "Immanuel" according to the view of one of the church fathers named Cyril of Alexandria.BAHASA INDONESIA ABSTRACT: Dalam Perjanjian Lama terdapat nubuat tentang Tuhan yang memberikan tanda bahwa seorang anak dara akan mengandung dan melahirkan seorang anak laki-laki, dan ia akan menamai-Nya Imanuel. Meskipun istilah ini terdengar tidak asing, kata Imanuel hanya disebutkan sebanyak 3 kali di dalam Alkitab, yaitu di dalam Yesaya 7:14, Yesaya 8:8, dan Matius 1:23. Kata "Imanuel" sendiri secara harfiah berarti "Allah menyertai kita". Kata ini merupakan sebutan yang merujuk pada kehadiran Tuhan dalam menyertai umat-Nya. Artikel ini akan membahas lebih jauh arti kata "Imanuel" menurut pandangan salah satu bapa gereja yang bernama Cyril dari Aleksandria.